ANTIFUNGAL Trycophyton rubrum AND Trycophyton mentagrophytes IN LIQUID BATH SOAP FERMENTED PROBIOTIC KOMBUCHA FLOWER TELANG (Clitoria ternatea L) AS A PHARMACEUTICAL BIOTECHNOLOGY PRODUCT - Pamungkas, Barolym Tri; Safitri, Ayu; Rezaldi, Firman; Andry, Muhammad; Agustiansyah, Lucky Dita; Fadillah, M. Fariz; Hidayanto, Fajar; Hariadi, Hari (Universitas Islam Negeri Ar-Raniry, 2022)
Telang flower kombucha (Clitoria ternatea L) is a functional probiotic drink that has antifungal properties. This study aimed to examine the antifungal activity of the probiotic bath soap formulation fermented kombucha telang flower against Trycophyton rubrum and Trycophyton mentagrophytes. This research method was carried out experimentally in an in vitro laboratory. The formulation of the fermented kombucha bath soap for the flower of telang was made with varying concentrations of 20%, 30%, and 40%. The preparation of probiotic bath soap for kombucha telang flower was tested for its antifungal activity against the bacteria T. rubrum and T. megantrophytes using the disc diffusion method. The working procedure includes the manufacture of bath soap preparations, and antifungal activity tests on the probiotic kombucha bath soap preparations of telang flower. The results of the study were positively correlated based on the one-way ANOVA test with f count greater than f table and showed that telang flower kombucha in the form of probiotic bath soap had antifungal activity against T. rubrum and T. mentagrophytes as a whole. The concentration of 40% was the highest concentration in the probiotic soap preparations fermented kombucha telang flower with an average inhibition zone diameter of 17.70 mm in T. rubrum species and 17.30 mm in T. mentagrophytes species. The average value of the diameter of the inhibition zone is included in the strong category.